Development Of Book Nook Online Bookstore Application With Prototyping Method - Kurdiana, Aulia Khalfani Izzati; Apriani, Debi; Agustiranti, Tifani; Darwis, Muhammad; Hendrowati, Retno (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2024)
Book Nook online bookstore business is a business that sells various kinds of books online. The business idea of selling books emerged as an effort to eradicate the act of book piracy. With the development of e-commerce, there is a desire to run an online book-selling business. This was done to overcome the problem of the high demand for books and to anticipate the increase in the rate of book piracy. Therefore, the Book Nook online bookstore requires an effective database system as a foundation for developing e-commerce applications. In this study, a relational database system was designed for the Book Nook online bookstore application with an emphasis on the prototyping and Unified Modelling Language (UML) model. The application development was implemented using the Flutter framework using the Dart language and MySQL database. The results of the implementation of the database were then tested using the black box method and the results proved that all the functions in the database were appropriate and running correctly.Keywords: UML, Online Book Application, E-commerce, Android Apps, Prototype